The Use of Charades Game in Teaching Vocabulary at SMPN 1 Pallangga - Bahsyar, Zulhijjah; Farahdiba, Syarifah; G, Hasriani (Journal of Excellence in English Language Education, 2025)
This study aims to determine the effectiveness of charades game in teaching vocabulary at SMP Negeri 1 Pallangga. The research used a pre-experimental method with a one-group pre-test and post-test design. The population were 7th-grade students from the 2024/2025 school year, with class VII.4, consisting of 45 students, chosen through cluster sampling. The instrument used in this study was a vocabulary test with four types of questions: fill in the blank, cloze-gap, definition, and sentence writing, totaling 20 items. The analysis of pre-test and post-test scores showed a significant improvement in students' vocabulary after using the charades game. The t-test result was 13.576, which is higher than the t-table value of 2.015, and the 2-tailed significance was less than alpha (α) 0.001 < 0.05. This means the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. In conclusion, the charades game is effective in improving vocabulary skills among students at SMPN 1 Pallangga.